1987
DOI: 10.1002/ana.410220108
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic‐dependent cognitive deficits in Parkinson's disease

Abstract: In a double-blind cross-over study, the effects of a subthreshold dose of scopolamine (0.25 mg) on memory were compared in 32 control subjects and 32 parkinsonian patients who were without any sign of intellectual and mnemic impairment. Although the scores of the controls in the memory test battery showed no deterioration after the administration of scopolamine, the same dose resulted in significantly reduced memory performance in parkinsonian patients in two tests which involved the recognition of meaningless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(72 citation statements)
references
References 24 publications
5
65
0
2
Order By: Relevance
“…Clock Setting and Clock Recognition tests. Dubois et al [34] have also found that, in Parkinson's disease, sub threshold doses of an anticholinesterase drug, scopol amine, impaired performance on complex visual tasks that demand selective attention and sequential-program ming but not memory abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Clock Setting and Clock Recognition tests. Dubois et al [34] have also found that, in Parkinson's disease, sub threshold doses of an anticholinesterase drug, scopol amine, impaired performance on complex visual tasks that demand selective attention and sequential-program ming but not memory abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence also implicates other neurotransmitters such as acetylcholine in the cognitive manifestations of PD. 88,[103][104][105] …”
Section: Pathophysiology Of Executive Dysfunctionmentioning
confidence: 99%
“…Although the long-term effects of levodopa on the prevalence of dementia remain controversial (Rajput et at., 1984;Portin and Rinne, 1986), short-term confusional effects are well-recognized and specific cognitive functions may be affected (Gotham et at., 1988). Anticholinergic drugs produce memory loss and confusional states in demented PD patients (de Smet et at., 1982) and sub-threshold doses of anticholinergics impair visual memory of non-demented PD patients but do not affect normal subjects (Dubois et at., 1987). Clearly, it is essential to take account of current drug therapy in evaluation of the prevalence of dementia in PD and in investigation of the specific effects of additional drugs on cognitive function.…”
Section: Drugsmentioning
confidence: 99%